Papers and Posters Presentation - 2004 - Team, Editorial (South African Journal of Enology and Viticulture, 2017)
Papers and Posters Presented at the Joint International Conf ere nee on Viti cultural Zoning, 15 - 19 November 2004, Cape Town, South Africa. THEME I-A Worldwide Perspective on Viticultural Zoning THEME II - Methodological Approach to Zoning THEME Ill - Practical Application of Zoning THEME Vill - The Role of Soil Water Holding Capacity and Plant Water Relations in Zone/Terroir Expression THEME IX - Role of Harvesting Time/Optimal Ripeness in Zone/Terroir Expression THEME X - Role of Molecular Ecophysiology in Terroir Expression THEME XI - The Role of Mechanization in Zonefferroir Expression THEME XII - Tools for Optimizing Grape and Wine Quality